Hydrophilic hollow fiber pvdf ultrafiltration membrane incorporated with titanate nanotubes for decolourization of aerobically-treated palm oil mill effluent - Subramaniam, Mahesan Naidu (Elsevier Science Sa, 2017)
In this study, a novel polyvinylidene fluoride (PVDF) hollow fiber nanocomposite ultrafiltration (UF) hollow fiber membrane was fabricated by introducing titanate nanotubes (TNTs) into the membrane matrix. Prior to membrane fabrication, the properties of TNTs were characterized using TEM, XRD and BET. The effect of TNTs loading (0–1.0%) on the properties of PVDF membrane such as cross section morphology, permeation and rejection capabilities were studied. Characterizations in term of membrane cross section morphology, contact angle and porosity were conducted. PVDF-TNT 0.5% nanocomposite membrane exhibited the most promising results, with colour removal of 58.9%, based on the American Manufacturers Dye Index (ADMI) value. Furthermore, these membranes were able to maintain flux values of 35.8 L/m2h for the duration of 240 min, showing very minimal signs of fouling. Analysis on flux recovery after simple pure water washing of the membranes also showed TNT loaded membranes are resistant towards fouling with 90% flux recovery and >95% rejection recovery rate when membranes were filtered for 5 continuous cycles.